2006
DOI: 10.1136/ard.2006.053918
|View full text |Cite
|
Sign up to set email alerts
|

Performance of various criteria sets in patients with inflammatory back pain of short duration; the Maastricht early spondyloarthritis clinic

Abstract: Among our selected cohort of patients with early IBP, the prevalence of SpA according to three different criteria sets is high. The ESSG criteria were the most sensitive, followed by the Amor criteria and the Berlin criteria. The modified New York criteria for ankylosing spondylitis appeared to be the most specific. In this cohort, the contribution of MRI and human leucocyte antigen B27 to purely clinical criteria in making a diagnosis of axial SpA was limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 14 publications
(9 reference statements)
2
40
1
7
Order By: Relevance
“…It is noteworthy that a significant proportion of patients in the above studies were diagnosed with AS in less than 2 42,45 or 5 44 years of disease. These findings suggest that diagnosis of AS in some patients made early in the disease course is at a time when the effect of TNF-α blockers may be significant.…”
Section: ) Additional Risk Has Been Identified In Prospective Cohmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that a significant proportion of patients in the above studies were diagnosed with AS in less than 2 42,45 or 5 44 years of disease. These findings suggest that diagnosis of AS in some patients made early in the disease course is at a time when the effect of TNF-α blockers may be significant.…”
Section: ) Additional Risk Has Been Identified In Prospective Cohmentioning
confidence: 99%
“…Heuft-Dorenbosch, et al 42 found that in patients with IBP for less than 2 years, ESSG 3 was the best instrument for classification of SpA, followed by criteria of Amor 2 , and lastly Rudwaleit, et al 41 . Of note, Heuft-Dorenbosch, et al 42 concluded that the contribution of HLA-B27 and MRI to the criteria by Amor 2 and ESSG 3 in diagnosing axial SpA was limited.…”
Section: ) Additional Risk Has Been Identified In Prospective Cohmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a subgroup of patients in a Dutch cohort developed structural changes rather early in the disease course; 20% of the patients with a history of inflammatory back pain of Ͻ2 years in duration had chronic structural changes in the SI joints (27). Although low-grade radiographic sacroiliitis has been proposed as a prognostic factor for the development of AS in patients originally classified as having undifferentiated SpA, only a minority of patients with nr-axSpA seem to develop definitive AS (28).…”
mentioning
confidence: 99%